Pengembangan Aplikasi SiBisa dalam Mewujudkan Program Smart City oleh Dinas Kependudukan dan Pencatatan Sipil Kota Medan - Marissa Septyani Situmorang; Siti Hazzah Nur Ritonga (Transpublika Publisher, 2025)
In realizing the implementation of a smart city in Medan, the city government has introduced several applications. One such application is the SiBisa Application, which aims to facilitate the public in managing administrative documents online, allowing them to do so anytime and anywhere. This study aims to examine and describe the development of the SiBisa Application in realizing the smart city program by the Medan Civil Registry Office. This research adopts a qualitative approach, employing Merilee S. Grindle's (1997) capacity development model, which consists of three indicators: human resource development, organizational strengthening, and institutional reform. The findings indicate that (a) Human resource development at the Medan Civil Registry Office remains inadequate in terms of the number of personnel, resulting in suboptimal training and education efforts; (b) The establishment of specialized teams, such as the SiBisa Service Implementation Team (Operators and Verifiers) and an Expert Team, whose roles align with their respective expertise and procedures, serves as a supporting factor in organizational strengthening; and (c) Institutional reform at the Medan Civil Registry Office is reflected in the transition from manual to digital services. However, a lack of public understanding of the technology provided remains a challenge.